A rare case of family suffering from Simpson-Golabi-Behmel syndrome with an uncommon manifestation in a mother and 2 sons - Kamil Możdżeń; Agnieszka Murawska; Julia Hypnar; Edward Pędziwiatr; Jakub Pośpiech; Kinga Kowalska-Duplaga (Termedia Publishing House, 2023)
Simpson-Golabi-Behmel syndrome (SGBS) is a rare X-linked disorder resulting from mutations in the genes GPC3 or GPC4. Symptoms of SGBS vary but commonly include overgrowth, craniofacial dysmorphias, and multiple birth defects. This syndrome has 2 subtypes, known as type I and type II. This report presents a case of SGBS occurring in several members of the same family, showing varying symptoms, including an 8-year-old boy, his older brother, mother, and mother's maternal half-brother. Exome sequencing identified the c.1159C > T variant of the GPC3 gene in all members of the family mentioned above. Family history suggests that the maternal grandmother of the reported boys also presented symptoms of SGBS, although she was never tested. The purpose of this study is to present various clinical manifestations of SGBS, which may assist clinicians. We also note the manifestation of SGBS in a female because it is uncommon for carriers of the gene to present symptoms.